2005
DOI: 10.3317/jraas.2005.001
|View full text |Cite
|
Sign up to set email alerts
|

Preventing end stage renal disease in diabetic patients — genetic aspect (part I)

Abstract: Diabetic nephropathy is a major cause of diabetesrelated morbidity and mortality; however the clinical course of the disease and the renal prognosis is highly variable among individuals. The current review will discuss the genetic influence on the development of end stage renal disease (ESRD) in diabetic patients and potential improvements to the current treatment strategy to slow the loss of kidney function in these patients. In this first part, the growing evidence that glucose-induced activation of the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 177 publications
(257 reference statements)
2
35
0
1
Order By: Relevance
“…Baseline characteristics of the patients according to the ACE insertion/deletion genotypes were similar, except for race and 2 , P Ͻ 0.05). The difference in BMI between genotypes was not significant after adjustment for race (P ϭ 0.557), whereas the trend to a difference in glycosylated hemoglobin became significant after adjustment for race (P ϭ 0.020).…”
Section: Resultsmentioning
confidence: 78%
“…Baseline characteristics of the patients according to the ACE insertion/deletion genotypes were similar, except for race and 2 , P Ͻ 0.05). The difference in BMI between genotypes was not significant after adjustment for race (P ϭ 0.557), whereas the trend to a difference in glycosylated hemoglobin became significant after adjustment for race (P ϭ 0.020).…”
Section: Resultsmentioning
confidence: 78%
“…Sums with increasing numbers of SNP markers (i.e. n) were formed, starting with the markers ranked highest S (n=1) = s (1) ; S (n=2) =s (1) +s (2) , and so on. The primary interest was to find the n of SNPs in S that reflects the association of this set of markers with the disease.…”
Section: Description Of Gene Variants and Genotyping Methodsmentioning
confidence: 99%
“…It has been established that the onset and progression of DN are genetically determined [2,3]. Ethnic differences in prevalence, uneven incidence over the time-course of the disease (culminating in the second decade of diabetes duration) [4], familial clustering in different populations for both type 1 and 2 diabetes [5][6][7][8][9][10][11][12][13], and the results of segregation analyses [14,15] suggest the existence of susceptibility genes for DN in addition to those leading to diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that ACE inhibitor therapy might be more benefit in the early stages of diabetic nephropathy, whereas in more advanced stages treatment appears to confer consistent renoprotection to all patients regardless of their ACE I/D genotypes (5). Among patients with overt nephropathy (43) an association between the I allele with a slower progression to doubling of serum creatinine or ESRD was observed. Also, it has been demonstrated that GFR decline over time was significantly slower in patients carrying one or two copies of I allele compared to D allele (44).…”
Section: Ace I/d Polymorphism and Response To Therapymentioning
confidence: 98%